Libraries and sustainability programs and practices for community impact - Aldrich, Rebekkah Smith; Antonelli, Monika; Ho, Adrian K. 1969-; Tanner, René 1963- (Chicago ALA Editions, 2022)
"This book explores a sustainability lens through which operational and outreach decisions can be made, discusses why sustainability matters to libraries and their communities, shares real-life examples of sustainability programming, and provides recommendations from library workers who have been active in putting sustainability into practice"--
Part I. Leadership -- Walking the Path to Sustainable Library Certification / Jill Davis, Jennifer Ferriss, and Lisa Kropp -- Rapid Library Disaster Response and Recovery for Community Resiliency / Michele P. Stricker -- Changing Staff Behaviors around Waste Reduction and Diversion Using a Community-Based Social Marketing Approach / Amanda Foster Kaufman, Brian Cohen, and Jeff Eller -- Part II. Planning -- Demystifying Sustainability in Library Buildings / Lan Ying Ip, Tamar arburg, Lauren Stara, and Andrea Bunker -- Using Permaculture in Rural Libraries to Help Save the World / April Griffith -- Sustainable Event Planning for Libraries and Library Organizations / Mandi Goodsett and Evan Meszaros -- Part III. Programming -- How Repair Events at Libraries Can Build Social Infrastructure and Create Sustainable Culture / Gabrielle Griffis -- Modelling Sustainable Choices: Practical Suggestions for Librarians Working with Children and Families Sustainable Events / Larissa M. Clotildes -- Connecting Community Through Sustainability: Seeds, Climate Action Kits and Repair Cafes / Jennifer Rowan, Aiyang Ma, and Karen Sharkey -- Part IV. Transformation -- Why We Can't Talk about Sustainability in Libraries without Also Talking about Racism / Erin Elzi -- Community-Based Librarianship: A First Step toward Sustainability / Ling Hwey Jeng, Ph.D. -- Libraries in the Doughnut Economy / Monika Antonelli, René Tanner, Rebekkah Smith Aldrich, and Adrian Ho.
Includes bibliographical references and index.
Keywords: Libraries -- Environmental aspects; Libraries and community -- United States